Assessing secondary students’ scientific literacy: A comparative study of suburban schools in England and Malaysia - Mohd Syafiq Aiman Mat Noor (ICASE, 2021)
This study sought to assess the level of secondary students’ scientific literacy in suburban schools in Malaysia and England, a research area which to date has not been fully explored in the literature. The study analysed the data using the OECD’s three domain-specific competencies of scientific literacy, namely: i) explain phenomena scientifically, ii) evaluate and design scientific enquiry, and iii) interpret data and evidence scientifically. To assess the level of secondary students’ scientific literacy in these contexts, the study applied the scientific literacy assessment instrument called the ‘Nature of Scientific Literacy Test’ (NOSLiT), first developed by Wenning (2006). The results indicated that the level of scientific literacy of English students was higher than that of Malaysian students across all three domain-specific competencies. Despite the fact that NOSLiT is a systematic and reliable instrument for assessing the level of students’ scientific literacy, the study found that OECD’s three domain-specific competencies of scientific literacy provided better insights into the level of secondary students’ scientific literacy in Malaysian and English suburban schools. It is suggested that future studies should use a qualitative approach to both data collection and analysis to understand the level of students’ scientific literacy in more detail.